A study of pressure-sinkage relationship used in a tyre-terrain interaction - Salman, Nihal Dawood; Kiss, Péter (International Journal of Engineering and Management Sciences, 2019)
The vehicle applies a normal load to the terrain, which causes sinkage and motion resistance. To forecast the normal pressure distribution on the interface of a vehicle–terrain and the tractive performance of a vehicle, the response of the terrain to normal load (which is characterized by pressure–sinkage relationship equations) must be measured. This paper presents the common conventional pressure sinkage models used in terramechanic and the modification that happened to this models. In addition the features of the new models.